MICROBIOLOGICAL MONITORING OF HOSPITAL ENVIRONMENT IN REGION VARNA - Gergana Nedelcheva; Gabriela St. Tsankova; Neli M. Ermenlieva; Tatina T. Todorova; Dayana Ts. Tsankova (Peytchinski Publishing, 2018)
The hospital environment is widely contaminated with opportunistic and pathogenic microorganisms and is considered as a source of outbreaks of nosocomial infections which are a worldwide phenomenon. Thus, it is clear that monitoring of the hospital environment is an essential element in the control of nosocomial infections. The purpose is to isolate and identify the microbes from hospital environment samples of different hospitals and healthcare services in the Region Varna and to analyze the risk that hospital environment poses in the region. This study was conducted over a period of 5 years from January 2012 to December 2016. A total of 12,673 different types of samples were collected and delivered quickly to the Laboratory of Microbiology of Regional Health Inspectorate Varna, where analyses were performed. We found bacteria in 816 of the tested objects and isolated a total of 29 bacterial species. The results show predominant Gram positive flora (71.81%), while Gram negatives represented only 28.19%. Prevention of nosocomial infections is a responsibility of all health-care workers. Microbiology laboratories should play a significant role in the attempts to minimize the occurrence of nosocomial infection through accurate identification of responsible organisms, timely reporting of laboratory data and participation in hospital infection control.